E-learning Method and University Life of Married Female Students in Patriarchal Social Structure in Sociological Perspective - Adhikari, Shukra Raj; Adhikari, Bhawani Shankar; Acharya, Ganga (Forum Ilmu Sosial, 2024)
Education is a process and means of human empowerment and social transformation. There are both formal and informal practices in educational processes. University is a unit of the formal education system that provides specific knowledge and skills in a universal context.  Face-to-face teaching is traditionally practiced as the teaching pedagogy in university education in Nepal. This paper analyzes the challenges and opportunities of e-learning for married female students within the university context under the patriarchal social structure. Married female students’ in-depth interviews based on the challenges and opportunities they faced in the e-learning system in university education have prepared the cases through their narratives as the primary date of the research. The cases have been collected by purposive sampling through the university level of students. The content analysis method has analyzed both primary and secondary data types. Married female students have been found to suffer from problems with individual devices, financial problems, computer literacy, regularity of electricity, and poor internet quality. Similarly, they have to face house-loaded problems during class time. They have the opportunity to manage household activities and adapt to new technology in learning, saving travel time and cost under the e-learning system of university life. The theoretical explanation of patriarchy only gets partially analog except for the partial application of its assumptions in the e-learning system, mainly for the married female students of the university.